High Dynamic Performance Control System of Motors Based on Load Torque Observer - LIU Yong; GAN Weiwei; MEI Wenqing (Kongzhi Yu Xinxi Jishu)
As for the effect of the control performance of the system by load torque disturbance, it studied and analyzed three types of load observers. Taking the vector control as an example, the load torque observed by load observer based on speed sensor was applied to control feed-forward compensation, so that the influence of load torque disturbance was reduced and the system’s control performance was improved. Simulation and experiment results proved the effectiveness of the load observer and the feed-forward control strategy.